Use of laminated timber in the construction of high-rise buildings, on the example of implementations from western countries - Dmitruk, Michał (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2020)
The architecture of modern, 20th and early 21st century high-rise buildings is primarily associated with materials such as steel, glass and concrete. With the advancement and popularity of laminated timber construction in western countries the use of wood as a structural component in high rise buildings brings many economic, technological and logistical benefits. Laminated timber is more flexible, lighter and often more durable than typically used materials in construction. Thanks to cross lamination technology, buildings are able to obtain significant heights while maintaining appropriate structural requirements. This material turns out to be easier to transport, and with proper prefabrication, will also speed up the construction processes at a reduced cost. Timber is an eco-friendly material, that with properly managed forests ensures a sustainable, renewable construction supply. This minimizes the cost to the environment by reducing CO2 emissions. The main obstacle to the implementation of this technology at a larger scale are numerous legal restrictions regarding strength and fire resistance. The research and implementation examples cited in the article below show that laminated wood is able to maintain appropriate structural requirements, ensuring the durability and safety of its occupants.